(untitled) (PAKISTAN JOURNAL OF LAW, ANALYSIS AND WISDOM, 2023)
This article emphasises the need of improving environmental protection through the application of international criminal law, as described in the International Criminal Court’s Rome Statute. After offering a brief summary of how international criminal law treats environmental protection during both times of war and peace, it is clear that the existing system falls short of maintaining effective environmental safeguards. This study contends that there is no compelling reason in international criminal law to regard environmental harm differently depending on whether it happens during war or peacetime. Instead, it indicates that using an eco-centric approach to environmental protection, which prioritises the environment over human interests, will improve environmental protection more successfully. As a result, the paper proposes for the Rome Statute to include a new comprehensive and eco-centric international crime targeting environmental harm. The paper then examines previous suggestions for such a crime and provides insights into its distinctive qualities. It focuses on identifying the level of severity necessary for the new crime and defines the fundamental mental state (mens rea) conditions that must be met.